Diet-dependent gene expression highlights the importance of Cytochrome P450 in detoxification of algal secondary metabolites in a marine isopod. Issue 1 (December 2018) - De Wit, Pierre; Yamada, Keith; Panova, Marina; André, Carl; Johannesson, Kerstin
Abstract Isopods of the genusIdotea have an unusual ability to feed on algae containing high amounts of chemical defense molecules, such as species of the generaFucus andUlva . In this study, we compared gene expression patterns ofIdotea balthica individuals fed withFucus vesiculosus to individuals fed withUlva lactuca . We generated the first-ever transcriptome assembly for this species, and found 3, 233 differentially expressed genes across feeding regimes. However, only a handful of biological functions were enriched with regard to differentially expressed genes, the most notable being "alkaloid metabolic process". Within this category, we found eight differentially expressed cytochrome P450 (CYP) unigenes, all of which had a higher expression in theU. lactuca diet treatment. A phylogenetic analysis showed that the differentially expressed CYP genes are closely related to a CYP gene described from the hepatopancreas of the spiny lobsterPanulirus argus, and we hypothesize that these transcripts are involved in metabolite detoxification. This is a first step in the understanding of this algae-grazer interaction, and will form a basis for future work to characterize cytochrome P450 functioning in marine crustaceans.